Factors influencing investment decisions of individual investors at Nepal stock exchange - Adhikari, Prem Lal (Management Dynamics, 2020)
The behavior of individual investors is concerned with choices regarding purchasing small quantities of securities for their own account. Investment options are also supported by decision-making instruments. It Is assumed that information structure and the market related factors systematically affect the investment decisions of individuals as well as market outcomes. The main purpose of the analysis was to identify the factors affecting individual investors’ investment decisions on the Nepal Stock Exchange. The study was conducted on the 214 responses received from the individual investors based on the random sampling method Data for the research were collected using a structured questionnaire distributed to the respondents. The questionnaire constituted 35 items. The respondents were individual investors. In this study, data were analyzed using frequencies, mean scores, standard deviations, percentages, and factor analysis techniques. The study confirmed that there appears to be a certain degree of correlation between the factors defined for the average equity investor by behavioral finance theory and prior empirical evidence. The researcher explored that the most significant factors shaping individual investment decisions were: statement of the government officials, expected capital increase, firm’s status in industry, diversification purpose, the attractiveness of non-stock investment, ease of obtaining borrowed funds, opinions of the firm’s majority stockholders, family member opinions, recent price movement in a firm’s stock, fluctuations in the stock index, rumors, expected corporate eating, stock marketability, the results of technical analysis, the dividend paid, perceived ethics of firm, the reputation of the firm’s shareholders, and feeling for a firm’s product and services. The results of this research will provide an understanding of the different decisions to be taken by investors on the basis of the prevailing factors and the possible consequences of each decision. The analysis would also help to recognize the most significant factors in the behavior of the company’s investors as their potential policies and plans will be impacted as the investment decisions of investors will determine the strategy to be used by the company.